Characteristics of Winter Clouds and Precipitation over the Mountains of Northern Beijing. (14th December 2017) - Ma, Xincheng; Bi, Kai; Chen, Yunbo; Chen, Yichen; Cheng, Zhigang
Abstract : There are few studies which reported the characteristics of winter clouds and precipitation in the Haituo Mountains of Northern Beijing where the 2022 Winter Olympic Games will be held. This paper outlines comprehensive datasets, including the surface measurements, remote sensing and aircraft measurements, to study cloud and precipitation characteristics over the mountainous terrain. The analysis results show (1) high-level trough and vortex were the main weather system in all 12 cases. (2) 58% of precipitation occurred only at night, and only 8% of snowfall occurred only at daytime, but under the surface inverse trough snowfall (in 4 of the 12 cases) persisted from night to day peaking at 20 hours; Snowfall persisted at least 3 hours in 83% of the snowfall, 5–10 hours in 50% of cases, and more than 10 hours in 33% of the storms. In 67% of cases, the maximum snowfall occurred within the initial 1-2 hours. (3) In 12 cases, 83% of orographic clouds reached Yan Jiaping, after increased southwesterly winds, resulting in visibility below 100 m. (4) during snowfall, The dominant wind direction is southwest. The start of the snowfall corresponded with an increase in southwesterly wind. The snowfall is maintained according to with the strengthening of southwesterly wind and dissipated accordingly with the receding of southwesterly wind. Whenever the snowfall stopped, the northwest wind was strong at all heights. (5) The first peak value of integral liquid water appeared in the early stage of snow, and we also observed integral liquid water increases with orographic cloud uplift, presenting potentially favorable seeding opportunities in 10 cases. (6) The primary crystal habits collected at Yan Jiaping during steady snowfall were rimed and aggregated planar dendrites.